Study of antioxidant enzymes activity during rooting in Adhatoda Vasica under different triazole compounds - Panneerselvam, M. Gnana Mani, R. (Journal of Phytology, 2015)
Medicinally important plant species, Adhatoda vasica belonging to the family Acanthaceae was selected for the present investigation in order to study the comparative effects of traditional as well as non-traditional growth regulators. The traditional growth regulator selected was IBA and non-traditional one was Hexaconazole and triadimefon. Antioxidant enzymes activities like SOD, APX and CAT were estimated from control as well as treated plants. The activities of antioxidant enzymes like SOD, APX and CAT were increased with TDM, HEX and IBA treatments in Adhatoda vasica plants. The enhancement was significant on all sampling days. These preliminary results prove TDM and HEX as potential growth regulators which can be used to enhance the antioxidant properties of Adhatoda vasica, thereby make it an economically valuable medicinal plant.